The Hsp40 J-domain modulates Hsp70 conformation and ATPase activity with a semi-elliptical spring - Bascos, Neil Andrews; Mayer, Matthias P.; Bukau, Bernd (Protein science, 2017)
Regulatory protein interactions are commonly attributed to lock-and-key associations that bring interacting domains together. However, studies in some systems suggest that regulation is not achieved by binding interactions alone. We report our investigations on specific physical characteristics required of the Hsp40 J-domain to stimulate ATP hydrolysis in the Hsp40-Hsp70 molecular chaperone machine. Biophysical analysis using isothermal titration calorimetry, and nuclear magnetic resonance spectroscopy reveals the importance of helix rigidity for the maintenance of Hsp40 function. Our results suggest that the functional J-domain acts like a semi-elliptical spring, wherein the resistance to bending upon binding to the Hsp70 ATPase modulates the ATPase domain conformational change and promotes ATP hydrolysis.